Performance Evaluation and Analysis of LightCert4IoT Using Cooja-Contiki Simulator - David Khoury; Samir Haddad; Patrick Sondi; Gaby Abou Haidar; David Semaan; Jinane Sayah (IEEE Access)
Recently, the focus on the Internet of Things (IoT) has rocketed in parallel with the evolution of mobile fifth-generation (5G) networks. To fully utilize IoT, which wirelessly connects billions of devices, a 5G network is essential. However, the provision of user’s certificates exposes the network to serious security threats. The LightCert4IoT leverages the advantages of EDGE nodes with blockchain technology and smart contracts to address the existing challenges of PKI (Public Key Infrastructure) certificates in IoT devices, which neatly achieves certificate issuance, update, and revocation more securely and efficiently. An end-user issues a self-signed certificate and lets Local Registration Authorities (LRAs)/EDGE nodes to verify and validate the binding identity signed certificate of the users through a blockchain such as Ethereum. This work analyzes the performance of LightCert4IoT in IoT devices by utilizing the Cooja-Contiki simulator. The results show reduced energy consumption and memory size when compared to the conventional X509 certificate. In conclusion, the LightCert4IoT meets the requirements of major IoT device constraints. The paper also addresses the security threats with the widespread use of IoT devices and analyses the adversary on security level from the authentication based on hardware token and blockchain and deploying firewall to protect servers against malicious attacks like DDOS. Scalability, resource limitations, and privacy concerns are analyzed as IoT devices handle sensitive information, and the transparent and immutable nature of blockchain can raise data protection. Analysis of Network partitioning challenge and communication overhead